On Approximation by an Absolutely Convergent Integral Related to the Mellin Transform - Antanas Laurinčikas (Axioms, 2023)
In this paper, we consider the modified Mellin transform of the product of the square of the Riemann zeta function and the exponentially decreasing function, and we discuss its probabilistic and approximation properties. It turns out that this Mellin transform approximates the identical zero in the strip <semantics>{s∈C:1/2<σ<1}</semantics>.